Holy office "familiaturas" and the learned magistracy in overseas Portugal (Brazil, 18th century) - Camarinhas, Nuno (Revista de História, 2016)
The eighteenth century represents an increase in size and complexity of the judicial structure of the Portuguese crown in Brazil. Career opportunities flourish and there is a double movement of agents: on the one hand, judges who come from the kingdom; on the other, a growing number of Brazilian-born judges who start a career in Justice. Based on the data collected on the qualifications to be member of the Holy Office, this text isolates the learned judges that served in the Portuguese territories of America, trying to understand the role played by the familiatura in the progression of their career, and their possible inclusion in recruitment or appointment networks in the Coimbra-Lisbon axis.